A study of the vertical sections of leaves and their blades in some species belonging to the families Chenopodiaceaa and Compositae. growing wild in Karbala governorate (Journal of the College of Basic Education, 2022)
The current research focused on some anatomical characteristics of leaves and blades of species of my family:Chenopodiaceae, Chenopodium murale L.Halocnemum strobilaceum (Pall.) M. Bieb.Haloxylon salicornicum (Moq.) Bunge ex. Boiss.Salicornia herbacea L. ,Compositae (Asteraceae), Carthamus oxycantha M.B.Launaea capitata (Spring.) Dany , Launaea mucronata (Forsk.) Muschl.Rechardia tingitana (L.) Roth.The leaves of the studied plants differed in the thickness of the layers of the epidermis (cuticle) and the epidermis, and whether the leaf was bi-faceted or unilateral. For the first time for some species, anatomical sections were taken for reduced squamous leaves in Halocnemum strobilaceum, Haloxylon salicornicum, and Salicornia herbacea, where these characteristics are not studied at the country level. The researcher did not find similar research in the Arab world.